Extending the Theory of Planned Behavior In Explaining Malaysian Tourists' Revisit Intention to Temajuk Beach - Udin Saryono; Jamal Abdul Nasir Shaari; Heriyadi (Asian Journal of Economics, Business and Accounting, 2026)
Indexed by Scopus/ERA